ECONOMIC MECHANISMS OF REGIONAL INDUSTRY DEVELOPMENT (Marketing Journal, 2025)
This scientific article comprehensively analyzes the economic mechanisms of regional industrial development. The study highlights the theoretical foundations of regional industrial development, the essence of economic mechanisms, and their impact on region al socio -economic development. It also reveals the role of state 587 support for industry in the regions, investment policy, financial and credit and tax mechanisms. The article also analyzes the importance of innovations, digital technologies, and foreign experience in ensuring the sustainability of regional industrial dev elopment. The results of the study serve to develop scientific conclusions and practical recommendations for improving regional industrial policy.
Keywords: regional industry; economic mechanisms; regional development; investment policy; industrial infrastructure; state regulation; innovation